Correlation of lactate threshold, VO2max, and running performance with 4.8 kilometer running performance - Epperson, C. E.; Buono, M. J.; Kolkhorst, F. W.; Reynolds, K. K.; Nanista, J. A.; Sheffield, R. D. (Medicine & Science in Sports & Exercise, 1999)
Female (N = 15) cross country runners were tested for lactate threshold, VO2max, and running economy, each being correlated with a time-trial time over 4.8 km. It was found that lactate threshold (r = .89), and VO2max (r = .66) were related to running time. Implication. Lactate threshold was the best single predictor of running a distance of 4.8 km.